Network simulation in NS-3 - Teo, Derrick Ren Jie. (2011)
The measurement of network throughput is often the concern of many people. A typical method of performing throughput measurement is to transfer a large file and measure the time taken to do so. The throughput is later calculated by dividing the file size by time.The aim on this project is to monitor the throughput of a simple wireless network and analyze various factors that can affect the throughput of a network. One Access Point and multiple Service Users will be deployed in this wireless network model; users will constantly transfer huge amounts of data through the network. A measurement will be done at the receiving end and results will be recorded and analyzed.